A competência do profissional contador e suas associações com seu desempenho - Orlandi, Rosilenia (2015)
The competitive scenario in which contemporary organizations are inserted, takes the need for constant development of professional accounting, so that they can follow and provides changes required by the context. As a result of this need, several authors have been studying and modeling to enable the Professional and organizational skills. This study sought to identify limitations and capabilities that can impact the performance of the counters to the challenges and requirements of the accountings profession. In order to investigate the associations between required skills and competence developed professional accounting, applied a questionnaire to a sample of 70 professionals working in an organization, the activities considered in the context of accounting. The results also show that there is little concern with the skills considered managerial or management. The results of the analysis of the professional skills required, compared to self-assessment of the professional will serve as an inducer for discussions and reflections and trainings.